A semantic analysis of the fishery vocabulary of the Hulu dialect of Banjarese - Muhammad Rafiek; H. Rustam Effendi (Studies in English Language and Education, 2022)
This study aimed to examine the fishery vocabulary in the Hulu dialect of Banjarese (upper river dialect) at the Central and North Hulu Sungai Regencies, Kalimantan, Indonesia. Data collection techniques were carried out by observation, interviews, and recording with 23 native speakers of the Banjarese language. They were permanent residents in the study locations, male and female residents aged 25-70, and they knew about their traditional fishing activities. Semantic analysis was used in scrutinizing the data. The initial vocabulary data from the informants was first identified and described. Each lexeme of the fishery vocabulary in the Hulu dialect of Banjarese was analyzed based on its lexical meaning, grammatical meaning, and semantic function. The words were then explained, paraphrased, and further categorized based on their types of meaning and function. The results showed that the fishery vocabulary of the Hulu dialect of Banjarese has 30 lexical meanings, comprising 28 nouns and two verbs. They are categorized into five types: (1) fishing gear, traps, and net, (2) fish containers, (3) fishing bait, (4) fish species, and (5) fishing activities. The fishery vocabulary in the Hulu dialect of Banjarese depicts the cultural wealth of these people. These lexemes can be maintained if the people continue to preserve the use of environment-friendly fishing gear that depicts their environmental and local wisdom.